Magnesium and Microelements in Older Persons - Veronese, Nicola; Barbagallo, Mario (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In recent years, the interest in magnesium and in microelements in older people has exponentially increased. The deficiency of either magnesium and microelements, in fact, is associated with several negative outcomes in older people. Therefore, in this book, we decided to report the most novel and important research findings regarding these important topics. In particular, authoritative authors in the field of nutritional research in older people reported their experience in magnesium research, including articles on metabolic and cardiovascular aspects of magnesium deficiency. Moreover, we speculated the importance of magnesium in infectious diseases, including COVID-19. In this book, we also report some important findings regarding other microelements, such as iron and sodium or potassium, extremely important in older people.